Darkness now visible : patriarchy's resurgence and feminist resistance / Carol Gilligan, David A. J. Richards. - Gilligan, Carol, 1936-; Richards, David A. J. (Cambridge University Press, 2018)
In the fall of 2016 those promoting patriarchal ideals saw their champion Donald Trump elected president of the United States and showed us how powerful patriarchy still is in American society and culture. Darkness Now Visible: Patriarchy's Resurgence and Feminist Resistance explains how patriarchy and its embrace of misogyny, racism, xenophobia, homophobia, and violence are starkly visible and must be recognized and resisted. Carol Gilligan and David A. J. Richards offer a bold and original thesis: that gender is the linchpin that holds in place the structures of unjust oppression through the codes of masculinity and femininity that subvert the capacity to resist injustice. Feminism is not an issue of women only, or a battle of women versus men - it is the key ethical movement of our age.